EMPLOYABILITY ENHANCEMENT THROUGH SOFT SKILLS: A STUDY OF MANAGEMENT EDUCATION IN NAGPUR (International Journal of Food and Nutritional Sciences, 2022)
In today's competitive job market, employability extends beyond academic knowledge and technical skills, emphasizing the significance of soft skills such as communication, teamwork, problem-solving, and emotional intelligence. This research investigates the impact of soft skill training on the employability of management graduates in Nagpur. Through a comprehensive review of existing literature and empirical analysis, this study aims to understand how soft skills are integrated into management programs and their effectiveness in enhancing employability. Data was collected from management students, faculty members, and industry recruiters through surveys and interviews to gauge the current state of soft skill training and its perceived impact on employment prospects. The findings highlight a positive correlation between soft skill proficiency and employability, demonstrating that graduates with well-developed soft skills are more likely to secure employment and succeed in their careers.